Cybersecurity and the digital revolution (on the example of the civil and military domain) - Lech Majewski (Przegląd Komunikacyjny)
Abstract: The emergence of new digital technologies creates new opportunities for deve- lopment and building material capabilities, but also brings significant changes to social life, the legal dimension, and ethics. It can be confidently stated that whoever utilizes the possibili- ties offered by artificial intelligence, space, and cyberspace faster and better will shape the future of the world, create a new civilization, and change its fundamental operations. This process has already begun. The world’s largest military powers prioritize digital technologies, autonomous and unmanned systems—their integration with manned aircraft or crewed ves- sels, artificial intelligence, and the utilization of space and cyberspace. It is important to em- phasize that these actions enable real-time combat operations. A cognitively distorted world is emerging, making it difficult to objectively assess existing situations. For instance, the United States, Europe, China, and Russia evaluate situations differently. China’s political system allows it to more easily and quickly dominate the cyber domain. China is progressively gai- ning technological superiority, mastering new technologies without facing civilizational or cultural objections.